(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Tax indicators include tax collection, tax arrears and tax risk, as well as other important indicators. Ensuring the connection between them helps to increase the efficiency of tax administration in the tax system. However, these processes imply extremely complex economic relations, so scientific research aimed at solving existing problems through their scientific analysis is of great importance. This scientific article (scientific dissertation) examines these issues.